2019
DOI: 10.1136/sextrans-2019-054096
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy-based sexual health services: a systematic review of experiences and attitudes of pharmacy users and pharmacy staff

Abstract: BackgroundPharmacies are increasingly providing services related to contraception and STIs. Identifying pharmacy staff’ and users’ experiences and attitudes relating to sexual health services is critical to understand users’ needs and examining how pharmacy staff can most effectively contribute to patient-centred care. This systematic review aimed to examine pharmacy staff and pharmacy users’ experiences and attitudes towards the delivery of a large range of sexual health services.MethodsSeven electronic datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…32 Similarly, Gauly et al reported in a systematic review that pharmacy users appreciated the convenience and easy access of pharmacies for SRH services and felt comfortable discussing sexual health with the pharmacist. 36 However, Gauly et al noted conflicting results about individuals' views on privacy. Some patients appreciated the privacy level provided in pharmacies while others expressed concerns about being overheard by other clients when talking to the pharmacist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Similarly, Gauly et al reported in a systematic review that pharmacy users appreciated the convenience and easy access of pharmacies for SRH services and felt comfortable discussing sexual health with the pharmacist. 36 However, Gauly et al noted conflicting results about individuals' views on privacy. Some patients appreciated the privacy level provided in pharmacies while others expressed concerns about being overheard by other clients when talking to the pharmacist.…”
Section: Discussionmentioning
confidence: 99%
“…30 Other reviews have also focused on pharmacists' and users' knowledge, attitudes, experiences and perspectives related to contraception as well as a broader spectrum of SRH services. [31][32][33][34][35][36] Overall, the available literature highlights positive users' experiences, implementation is feasible, and also some challenges for pharmacy staff and users. However, these reviews have not addressed the topic from the service organisation, implementation and delivery perspective.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Each study was assessed using five assessment points, and then an overall rating system was applied to each study. 17 Studies were given an overall rating of high quality if four or five criteria were met, moderate quality if three criteria were met, and low quality if two or less criteria were met. 17 …”
Section: Methodsmentioning
confidence: 99%
“…To inform policy and research in the UK and countries with similar economic backgrounds, literature pertaining to Organisation for Economic Co-Operation and Development (OECD) member countries was used [13]. All settings in which contraceptive methods are available were included.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%